Incidence of cervical spine fractures on CT: a study in a large level I trauma center (2020)
Introduction/purpose Though spinal fractures constitute a minority of all traumas, the financial burden imposed is immense especially following cervical spine trauma. There have been several papers in the past describing the incidence of cervical spine fractures. In this paper, we report the incidence of cervical spine fractures and correlate with demographic information and cause of injury and review the mechanism of fractures. Materials and methods We performed retrospective analysis of 934 patients who had undergone CT scan for cervical spine trauma at our institute which includes 16 hospitals and one level I trauma center over a period of 2 years. This list was created from a wider database of 13,512 patients imaged for suspected cervical spine injury. All patients who had at least one positive finding on CT were included in this study irrespective of any demographic difference. Each patient was analyzed by reviewing the medical records, and correlation was sought between demographics and cause of injury. Results In our study, the peak incidence of cervical spine trauma was in the age group of 21–30 years followed by 31–40 years with a male:female ratio of 2.1. The major cause of injury in the study population was motor vehicle accidents (66.1%), followed by fall from height of less than 8 ft (12.2%). With regard to the ethnic distribution, Caucasians (46.9%) constituted the major population followed by Hispanic population (23.3%). C1 and C2 were observed to be more frequently fractured as compared with the subaxial spine. Incidence of C2 fractures (188 levels) was higher as compared with C1 (102 levels). Incidence of body and lateral mass fractures was marginally higher as compared with odontoid fractures. C7 (50 levels) was the most fractured vertebral body in the subaxial spine followed by C6 (35 levels) and C5. Conclusion Spinal trauma is on the rise and it helps to know the factors which can guide us for better management of these patients. We can utilize these results to prognosticate and streamline clinical management of these patients.